Mobile Thresholds, Immobile Phones: Staging Migration, Return, and the Empty Home in Recent Ecuadorian Theater - Amalia Gladhart (Studies in 20th & 21st Century Literature, 2008)
In the past decade, hundreds of thousands of Ecuadorians have emigrated, principally to Spain and the United States. A growing body of recent Ecuadorian plays has treated the experiences of the migrants and, tellingly, the experiences of those left behind. This essay focuses on three plays that present migration as a kind of threshold, a space of transition that is paradoxically temporary yet solid: Con estos zapatos me quería comer el mundo ‘With These Shoes I Meant to Take on the World,’ (2002) by Jorge Mateus and Pablo Tatés; El pueblo de las mujeres solas ‘The Village of Solitary Women,’ (2005) by Jorge Mateus; and La Travesía ‘The Crossing,’ (2002) by Nixon García. These plays present the ambivalent situation of the migrant as one of both frustration and possibility. All three plays employ small casts of characters to explore the individual transitions faced by the migrant and to evoke the nostalgia and ambivalence that surround the possibility of return. The stage, endlessly redefined, mimics, in some ways, the provisional space occupied by the migrant. These plays exploit that resemblance, using the malleability of the stage space to perform a migration that is not yet finished or resolved. The plays also raise vital questions about the staging of a specific Latin American experience in different national or regional contexts. The staging of liminality and displacement is central to these plays as the characters negotiate unfamiliar languages and landscapes, including the previously familiar landscape of a home changed by the absence of the migrant.
Keywords: Ecuador; Ecuadorian theater; migrants; migration; con estos zapatos me quería comer el mundo; Jorge Mateus; Pablo Tatés; el pueblo de las mujeres solas; la travesía; Nixon García; space